Leaf carbohydrate metabolism in Malbec grapevines : combined effects of regulated déficit irrigation and crop load - Dayer, Silvina; Prieto, Jorge Alejandro; Galat Giorgi, Mirta Eugenia; Perez Peña, Jorge Esteban (2017)
Background and aims: Regulated deficit irrigation and crop load adjustment are viticultural practices used to improve grape and wine composition. Our objective was to evaluate the combined effect of irrigation and crop load levels on leaf photosynthesis, accumulation of non-structural carbohydrates and leaf carbon utilisation during the season. Methods and Results: The trial started in 2006 in a Vitis vinifera L. Malbec vineyard in Mendoza. Two irrigation levels (100% and 25% of reference evapotranspiration) and two crop loads (20 and 10 bunches per vine, set at veraison) were studied. During the 2009/10 season, diurnal dynamics of leaf water potential, photosynthesis and carbohydrate concentration were determined at anthesis, veraison and harvest. Deficit irrigation reduced leaf starch concentration at veraison and increased soluble sugars. High-crop load reduced leaf starch concentration at veraison. Starch turnover was correlated with photosynthesis during the previous day. Conclusions: Deficit irrigation had a greater effect on carbon allocation between soluble sugars and starch than on total carbohydrate production. Effects of deficit irrigation and crop load operated independently. Significance of the Study: This experiment improved our knowledge of carbon assimilation and allocation during the season, which may assist the development of management practices to stabilise yield and fruit composition.